GOVERNMENT EFFORTS TO INCREASE THE ROLE OF WOMEN IN DEVELOPMENT IN PANCANA VILLAGE, TANETE RILAU DISTRICT, BARRU DISTRICT - Muliati (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal